2015
DOI: 10.4172/2161-119x.1000207
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile Laryngeal Papillomatosis in Benin: Epidemiological, Diagnostic, Therapeutic and Evolutionary Aspects

Abstract: Introduction: To describe the epidemiological profile of patients with laryngeal papillomatosis, to identify diagnostic aspects and evolution after treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
1
0
0
Order By: Relevance
“…Similar observations were found in our study in which under 5 year patients had the highest prevalence while the adolescent age group (15-19 years) had the lowest prevalence 1 (2%), this can possibly be due to the fact that laryngeal papillomatosis tends to subside at this age or upon attaining puberty. Although most of the studies show males to be more affected [3,4,7,8], our study showed that females are more affected 11 (57.9%) than males 8(42.1%) for patients under 5years and in AOLP in which females were 4 (57.1%) while males 3 (42.9%), other age groups agree with findings from the previous studies. However, generally males have high prevalence in JOLP as well as AOLP.…”
Section: Discussionsupporting
confidence: 89%
“…Similar observations were found in our study in which under 5 year patients had the highest prevalence while the adolescent age group (15-19 years) had the lowest prevalence 1 (2%), this can possibly be due to the fact that laryngeal papillomatosis tends to subside at this age or upon attaining puberty. Although most of the studies show males to be more affected [3,4,7,8], our study showed that females are more affected 11 (57.9%) than males 8(42.1%) for patients under 5years and in AOLP in which females were 4 (57.1%) while males 3 (42.9%), other age groups agree with findings from the previous studies. However, generally males have high prevalence in JOLP as well as AOLP.…”
Section: Discussionsupporting
confidence: 89%